How new media marketing activities affect customer loyalty in Islamic Jordanian banks - Tahat, Zuhair Yassin; Al-Kadi, Amjad Bader; Saad, Hamza; Al Hadeed, Ali; Habes, Mohammed; Elareshi, Mokhtar; Al Olaimat, Farhan (Frontiers in Communication, 2025)
This study aims to explore the impact of various factors associated with new media marketing (NMA) activities on brand trust and customer loyalty, focusing on the experience of Jordan Islamic Bank (JIB). Drawing on Relationship Marketing Theory (RMT) and a PLS-SEM methodology, the research analyzes the key dimensions of digital marketing activities—participation, openness, relationship building, and community building—and their role in enhancing customer loyalty. Data was collected from a sample of 355 bank customers via an online survey using a convenience sampling technique. Results showed that openness and community building had a significant impact on enhancing customer engagement, while the relationship between participation and brand trust appeared more complex. Building online communities also emerged as one of the most significant determinants of customer loyalty. The study highlights the importance of developing a value-based, community-centric digital presence to ensure sustainable customer relationships. It also recommends aligning digital marketing strategies with cultural and religious values, which is particularly important in the context of Islamic banks.